Retinal vascular occlusions in open heart surgery. - Williams, I M (1975)
This study describes microthrombotic emboli (with their ultrastructure) and emboli of fat and of dimethylpolysiloxane with silica in the retinal microcirculation of two patients who died-each after his second open heart operation. The presence of silica was confirmed by electron probe x-ray micro-analysis.